Rethinking the Relationship Between Dating Services and the Hospitality Industry Through Speed Dating Events: A Partner Ecosystem Strategy - Yallop, Anca; Séraphin, Hugues; Hamdan, Omar Abou (Cognizant Communication Corporation, 2025)
This study aims to develop a conceptual framework for the relationship between the hospitality and dating services industries, theorising this relationship by focusing on the role of speed dating events as a connecting intersection. Several theoretical foundations, including value (co)creation, service ecosystems, cue utilisation theory, and criteria for feasible and sustainable partnerships, were adopted to conceptualise this relationship. The new conceptual framework of relational value (co)creation introduces a novel joint concept that integrates the cues of both industries while allowing each to retain its unique identity. This study contributes to the understanding of relationships between organisations from different but intersecting industries, highlighting that ‘control’ is a key agent influencing the level of trust between organisations operating in intersecting industries, whilst the development of new avenues for collaboration enhances mutual returns from partnerships within the service ecosystem and creates opportunities for ‘unsaturated’ business partnerships.
Keywords: 1503 Business and Management; 1504 Commercial Services; 1506 Tourism; Sport, Leisure & Tourism; 3504 Commercial services; 3507 Strategy, management and organisational behaviour; 3508 Tourism; Control; Hospitality Industry; Saturated/unsaturated Partnership; Speed Dating; Trust; Value (Co)creation